Negotiation of meaning in outside of the classroom group assignments: accounting for the how to understand the what of future mathematics teachers' learning (2011)
In this paper we illustrate how Wenger¿s theory of social learning can be used to account for phenomena of future teachers change in settings that are not usually studied, namely group work that future teachers do as they work on class assignments outside of class. We describe how we adapted Wenger¿s theory to the exploration of future mathematics teachers¿ learning and illustrate how the analysis of the audio taped interaction of a group of future teachers working out-side the classroom generated conjectures that help to explain their didactic knowledge development.